Soft Folding - Zhu, L.; Igarashi, T.; Mitani, J. (Computer graphics forum, 2013)
We introduce soft folding, a new interactive method for designing and exploring thin‐plate forms. A user specifies sharp and soft folds as two‐dimensional(2D) curves on a flat sheet, along with the fold magnitude and sharpness of each. Then, based on the soft folds, the system computes the three‐dimensional(3D) folded shape. Internally, the system first computes a fold field, which defines local folding operations on a flat sheet. A fold field is a generalization of a discrete fold graph in origami, replacing a graph with sharp folds with a continuous field with soft folds. Next, local patches are folded independently according to the fold field. Finally, a globally folded 3D shape is obtained by assembling the locally folded patches. This algorithm computes an approximation of 3D developable surfaces with user‐defined soft folds at an interactive speed. The user can later apply nonlinear physical simulation to generate more realistic results. Experimental results demonstrated that soft folding is effective for producing complex folded shapes with controllable sharpness.